Strategi Kepala Madrasah Dalam Pengembangan Budaya Literasi Sekolah Di MTs-Al-Mukhlishin Antibar - Ade Syahrizal; Akhmad Fauzi Hamzah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the headmaster's strategy in developing a literacy culture at MTs Al-Mukhlishin Antibar. The background of this research is based on the low literacy habits among students, caused by the suboptimal role of the headmaster in managing literacy programs. This research employed a descriptive qualitative method with data collected through observation, in-depth interviews, and documentation. The results show that the headmaster applied four main strategies: integration strategy by embedding literacy programs into the school's daily routines; intensive strategy by increasing the frequency of literacy activities; diversification strategy through varied reading activities; and defensive strategy by strengthening literacy habits and teacher role modeling. Furthermore, literacy culture management was supported by optimizing library facilities, implementing regular library visits, integrating literacy into the curriculum, and conducting routine supervision. This study concludes that the strategic role of the headmaster as an instructional leader significantly influences the strengthening of literacy culture in the madrasah environment. The developed literacy culture not only enhances academic skills but also shapes students' character to become literate, critical thinkers, and morally upright individuals in line with Islamic educational values.